Potential for Sugar Maple to Provide High-Quality Sawlog Trees at the Northern Edge of Its Range - Guillemette, François; Bédard, Steve (Forest Science, 2019)
Abstract The management of sugar maple (Acer saccharum) at the northern edge of its range is mainly oriented toward timber production, from trees of higher grades. However, both the quality of mature trees in natural stands and how the quality may vary depending on the silvicultural treatment are unknown, especially under northern conditions. The objective of this study was to describe the variation in stem quality of mature maple trees (diameter >33 cm) according to climatic, geographic or soil variables, and to evaluate the effects of a first selection cutting cycle on this quality. Annual temperature (1.7–4.1° C) was the most important variable explaining differences in the proportion of higher-grade trees, with a 16 percent gain associated with every additional increase in degrees Celsius. The practice of a first selection cutting was associated with an 11 percent gain in this proportion. Although the actual proportion of high-quality trees was below 35 percent on the coolest sites, a proper tree selection through silviculture could likely improve this proportion in future decades, whereas the potential effects of climate change are unclear.
Keywords: Guillemette_Francois

Comparing structural attributes in uneven-aged managed and unmanaged sugar maple stands - Gauthier, Martin-Michel; Bédard, Steve; Guillemette, François (Forestry: An International Journal of Forest Research, 2019)
Keywords: Guillemette_Francois

Widespread occurrence and spatial distribution of glyphosate, atrazine, and neonicotinoids pesticides in the St. Lawrence and tributary rivers - Montiel-León, Juan Manuel; Munoz, Gabriel; Vo Duy, Sung; Do, Dat Tien; Vaudreuil, Marc-Antoine; Goeury, Ken; Guillemette, François; Amyot, Marc; Sauvé, Sébastien (Environmental Pollution, 2019)
Keywords: Guillemette_Francois

Bark type reflects growth potential of yellow birch and sugar maple at the northern limit of their range - Gauthier, Martin-Michel; Guillemette, François (Plant Ecology, 2018)
Keywords: Guillemette_Francois

Predicting volume distributions of hardwood sawn products by tree grade in eastern Canada - Bédard, Steve; Duchesne, Isabelle; Guillemette, François; DeBlois, Josianne (Forestry: An International Journal of Forest Research, 2018)
Keywords: Guillemette_Francois